Alleviating Indigenous poverty through tourism: the role of NGOs. Issue 10 (9th August 2022) - Hoque, Md Ariful; Lovelock, Brent; Carr, Anna
Abstract: Tourism is acknowledged as a tool through which communities can achieve the United Nations' Sustainable Development Goals (SDGs), with non-governmental organisations (NGOs) highlighted as important development partners in this regard. This paper examines the role of NGOs in tourism-related poverty alleviation in the context of a rural Indigenous community in Bangladesh. Drawing on critical theory, a qualitative case study approach employed multiple methods including semi-structured interviews, focus group discussion and observation to analyse the NGO-tourism-Indigenous poverty nexus. Findings revealed that the sustainability of NGO project outcomes was affected by several issues, including: a limited community voice; community dependency upon NGOs; and the threat of community displacement. NGO interventions created some economic opportunities through facilitating the community's tourism involvement, for example through the provision of microcredit and training. However, multiple stakeholders' involvement and diverse goals complicated the enactment of an effective partnership (SDG17) for the community's poverty alleviation (SDG1). The study concludes that NGOs need to go beyond service delivery and adopt an advocacy role in order to address some of the underlying structural inequities faced by such communities. This would enable NGOs, government agencies and communities to work together to better capitalise on tourism's potential for Indigenous poverty alleviation.